Deepening the cognition of ultrasonic vibration's role on plastic deformation of 2219 aluminum alloy tube during ultrasonic surface rolling process - Zhang YuanQi; Zhan Mei; Fan XiaoGuang (Manufacturing Review)
This work aims to enhance the comprehension of the effect of ultrasonic vibration on the plastic deformation of 2219 aluminum alloy during ultrasonic surface rolling process (USRP). To this end, the finite element (FE) model of 2219 aluminum alloy surface rolling with and without ultrasonic vibration were established to explore whether ultrasonic vibration has effect on the plastic deformation. Furthermore, by comparing the plastic strain and the thickness of plastic deformation layer under different static force and dynamic impact force values, their contributions were discussed. The results show that for the thickness of plastic deformation layer, the effect of ultrasonic vibration is infinitesimal. The reason why the simulation result (∼2.6%) is smaller than the experiment result (∼5.8%) may be the influence of temperature and friction. According to simulation results, when static force is increased by 47.5% (from 400 N to 590 N), to obtain the same plastic strain or plastic deformation layer, the dynamic impact force needs to be lifted by about 17 times, 25 times, respectively. The contribution ratio of dynamic impact force to the thickness of plastic deformation layer is ∼5.5%, which is far less than that of static force. Therefore, the static force dominates the plastic deformation during USRP.